Financial Performance Analysis of PT Mayora Indah TBK 2021–2025 Period: Profitability, Solvency, and Liquidity Ratio Approach - Aprilia Eka Saputri; Ani Septiani; Anggi Mailani; Malika Saufura; Yernita Bago; Indriyani Aprilia Setiawan; Heriyati Heriyati (Nomico, 2026)
This study aims to analyze the financial performance of PT Mayora Indah Tbk (IDX: MYOR) during the 2021–2025 period using a financial ratio analysis approach that includes profitability ratios (ROA and ROE), solvency ratios (DAR and DER), and liquidity ratios (Current Ratio and Quick Ratio). Data are sourced from audited annual financial reports published on the Indonesia Stock Exchange. The analysis results show that the company's financial performance peaked in 2023 with an ROA of 13.59%, an ROE of 21.23%, a Current Ratio of 3.67 times, and a DER of 0.56 times, driven by post-pandemic economic recovery and raw material cost efficiency. Despite normalization in 2024–2025, all financial ratio indicators remained within a healthy range and above the consumer goods industry standard. The company's capital structure proved conservative with a DAR consistently below 43% and a DER below 0.75 throughout the observation period. This study concludes that PT Mayora Indah Tbk has strong financial fundamentals and is able to manage external challenges effectively.